Estudo das APIs Java para geração de gráficos com Swing e JavaFX - Both, Cesar Augusto (2015)
The development of applications consists of innumerable stages as to choose the platform and the technology, that will be used for the development and are of utmost importance and require attention. Being about platform desktop computer and programming language Java the availability of the APIs Swing and JavaFX exists. As Swing it is in a process of transition for JavaFX, it fits to the desenvolvedores of applications to analyse uses the penalty still to use Swing or they must be migrated for JavaFX. On the basis of this, this study it has as objective to analyse these two APIs and to verify important points for the generation of graphs, evaluating differences between them and to accomplish metric of performance capable to define a preferable option for the elaborated study.